YOUNG PEOPLE’S CONFIDENCE IN THE ROLES AND RESPONSIBILITIES OF LGBTQ+ MEMBERS OF THE HOUSE OF REPRESENTATIVES - Sathitsathien, Naiyana; Inchai, Puangtong (Journal of Social Science and Cultural, 2023)
The objective of this research were to study 1) the confidence level of youth towards the roles of LGBTQ+ members of the Parliament and 2) the knowledge and understanding of the roles of LGBTQ+ members of the Parliament. The sample group consisted of 347 students from Rajamangala University of Technology Tawan-ok, Bangpra Campus. The research was quantitative and employed the Yamane formula for sample selection. A questionnaire was used as a research instrument. The tools utilized for the research included frequency, percentage, mean, standard deviation, and t-test statistics. The research findings revealed that among the youth, 219 individuals, accounting for 63.1%, exhibited confidence, while 68 individuals, constituting 19.6%, were uncertain. Moreover, a significant difference was observed in the perception of the roles of LGBTQ+ members who are representatives in the Parliament. This distinction was noted among 60 individuals, representing 17.3% of the respondents. Regarding the confidence level of the youth towards the roles of LGBTQ+ members who are representatives in the Parliament, the overall average score was 3.56, indicating a high level of confidence. Considering each aspect individually, it was found that the role of being a representative of the people had the highest average score of 3.64. Following that, the roles related to legal matters had an average score of 3.55, roles involving legal regulations had an average score of 3.54, roles related to governmental administration had an average score of 3.52, and finally, the roles within political institutions had the lowest average score of 3.50. In conclusion, the youth’s confidence towards LGBTQ+ members who are representatives in the Parliament reflected the societal progress in terms of freedom rights. The selection of representatives depended on their duties as public representatives according to the law, and working for the people was essential appropriate, respectful Proud of the status of representatives of the Thai people.